The Oxford handbook of online intermediary liability - Frosio, Giancarlo F. (Oxford : Oxford University Press, 2020)
There are emerging legal, policy, and ethical issues facing online intermediaries that have so far received various inconsistent answers even within the same jurisdiction. To better understand the heterogeneity of the international online intermediary liability regime, The Oxford Handbook of Online Intermediary Liability is designed to provide a comprehensive, authoritative, and 'state-of-the-art' discussion of this topic. This book will review fundamental legal issues in online intermediary liability, while also describing advances in intermediary liability theory and identifying recent policy trends.
Mapping Online Intermediary Liability / Giancarlo Frosio -- The Marco Civil da Internet and Digital Constitutionalism / Luiz Fernando Marrey Moncau, Diego Werneck Arguelhes -- Intermediary Liability in Africa: Looking Back, Moving Forward? / Nicolo Zingales -- The Liability of Australian Online Intermediaries / Kylie Pappalardo, Nicolas Suzor -- From Liability Trap to the World's Safest Harbor: Lessons from China, India, Japan, Korea, Indonesia, and Malaysia / Kyung-Sin Park -- China's IP Regulation and Omniscient Intermediaries: Oscillating from Safe Harbour to Liability / Danny Friedmann -- A New Liability Regime for Illegal Content in the Digital Single Market Strategy / t Eduardo Bertoni -- From 'Notice and Takedown' to 'Notice and Stay Down': Risks and Safeguards for Freedom of Expression / Aleksandra Kuczerawy -- Monitoring and Filtering: European Reform or Global Trend? / Giancarlo Frosio, Sunimal Mendis -- Blocking Orders: Assessing Tensions with Human Rights / Christophe Geiger, Elena Izyumenko -- A Theoretical Taxonomy of Intermediary Liability / Jaani Riordan -- Administrative Enforcement of Copyright Infringement in Europe / Alessandro Cogo, Marco Ricolfi -- Accountability and Responsibility of Online Intermediaries / Giancarlo Frosio, Martin Husovec -- Addressing Infringement: Developments in Content Regulation in the US and the DNS / Annemarie Bridy -- Intermediary Liability in Russia and the Role of Private Business in the Enforcement of State Controls over the Internet / Sergei Hovyadinov -- Guarding the Guardians: Content Moderation by Online Intermediaries and the Rule of Law / Niva Elkin-Koren, Maayan Perel -- Algorithmic Accountability: Towards Accountable Systems / Ben Wagner -- Internet Jurisdiction and Intermediary Liability / Dan Jerker B. Svantesson -- The Equustek Effect: A Canadian Perspective on Global Takedown Orders in the Age of the Internet / Michael Geist -- Jurisdiction on the Internet: From Legal Arms Race to Transnational Cooperation / Bertrand de La Chapelle, Paul Fehlinger -- Remedies First, Liability Second: Or Why We Fail to Agree on Optimal Design of Intermediary Liability / Martin Husovec -- Empirical Approaches to Intermediary Liability / Kristofer Erickson, Martin Kretschmer -- The Civic Role of OSPs in Mature Information Societies / Mariarosaria Taddeo -- Intermediary Liability and Fundamental Rights / Christophe Geiger, Giancarlo Frosio, Elena Izyumenko -- An Overview of the United States' Section 230 Internet Immunity / Eric Goldman -- The Impact of Free Trade Agreements on Internet Intermediary Liability in Latin American
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 4, 2020).
Keywords: Liability (Law); Internet service providers -- Law and legislation; Online social networks -- Law and legislation